Reduced mitochondrial mass and function add to age‐related susceptibility toward diet‐induced fatty liver in C57BL/6J mice. Issue 19 (30th September 2016) - Lohr, Kerstin; Pachl, Fiona; Moghaddas Gholami, Amin; Geillinger, Kerstin E.; Daniel, Hannelore; Kuster, Bernhard; Klingenspor, Martin
Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major health burden in the aging society with an urging medical need for a better understanding of the underlying mechanisms. Mitochondrial fatty acid oxidation and mitochondrial‐derived reactive oxygen species (ROS) are considered critical in the development of hepatic steatosis, the hallmark of NAFLD. Our study addressed in C57BL/6J mice the effect of high fat diet feeding and age on liver mitochondria at an early stage of NAFLD development. We therefore analyzed functional characteristics of hepatic mitochondria and associated alterations in the mitochondrial proteome in response to high fat feeding in adolescent, young adult, and middle‐aged mice. Susceptibility to diet‐induced obesity increased with age. Young adult and middle‐aged mice developed fatty liver, but not adolescent mice. Fat accumulation was negatively correlated with an age‐related reduction in mitochondrial mass and aggravated by a reduced capacity of fatty acid oxidation in high fat‐fed mice. Irrespective of age, high fat diet increased ROS production in hepatic mitochondria associated with a balanced nuclear factor erythroid‐derived 2 like 2 (NFE2L2) dependent antioxidative response, most likely triggered by reduced tethering of NFE2L2 to mitochondrial phosphoglycerate mutase 5. Age indirectly influenced mitochondrial function by reducing mitochondrial mass, thus exacerbating diet‐induced fat accumulation. Therefore, consideration of age in metabolic studies must be emphasized. Abstract : Our study elucidated the early changes in liver physiology upon feeding a high fat diet investigated in three age groups of C57BL/6J mice. Intriguingly, the interaction between high fat diet and increasing age enforces the accumulation of fat in the liver while reducing mitochondrial mass and function.